2009
DOI: 10.1063/1.3119629
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wave second-harmonic generation using domain-disordered quasi-phase matching waveguides

Abstract: Second-harmonic generation in domain-disordered quasi-phase-matched GaAs/AlGaAs superlattice-core waveguides was demonstrated using a continuous wave fundamental source. Output second-harmonic powers of up to 1.6 W were measured when on a Fabry-Pérot resonance peak. Temperature-related bistable behavior was observed in both the fundamental and second-harmonic output when tuning either the input power or input wavelength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…This is within the accuracy for wavelength measurements using the OSA, but with continuous-wave inputs for both the pump and signal, there is likely to be significant heating of the sample. Hence the increase of the pump wavelength to maintain phase-matching could be in compensation for the thermo-optic effects causing a shift in the tuning curve, which was observed previously for SHG [14]. For a 1550.1 nm signal wavelength, the idler wavelength was found at 1620.7 nm.…”
Section: Optical Measurementsmentioning
confidence: 57%
See 2 more Smart Citations
“…This is within the accuracy for wavelength measurements using the OSA, but with continuous-wave inputs for both the pump and signal, there is likely to be significant heating of the sample. Hence the increase of the pump wavelength to maintain phase-matching could be in compensation for the thermo-optic effects causing a shift in the tuning curve, which was observed previously for SHG [14]. For a 1550.1 nm signal wavelength, the idler wavelength was found at 1620.7 nm.…”
Section: Optical Measurementsmentioning
confidence: 57%
“…Theoretical calculations from the superlattice electronic band structure have predicted that a large modulation in χ (2) of up to 100 pm/V can be obtained using this approach [13]. Using DD-QPM waveguides, we have demonstrated continuous-wave second-harmonic generation (SHG) [14] and type-II phase matched SHG [15]. In this paper, we report on difference frequency generation with GaAs/AlGaAs superlattice-core domain-disordered quasiphase matching waveguides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the SHG experiments performed with the most recent devices, the result has been the production of nearly 10 µW of second-harmonic power using 2-ps optical pulses at wavelengths around 1550 nm in the type-I interaction (TE polarized fundamental, TM secondharmonic), representing a nearly six-times increase over previous generation devices [84] and a conversion efficiency improvement of nearly an order of magnitude over the first demonstrations of superlattice core DD-QPM waveguides [97]. With the improvements made, the latest DD-QPM devices were capable of continuous-wave SHG [68] and type-II SHG (mixed TE/TM fundamental, TE second-harmonic) [98] with internally generated second-harmonic powers in excess of 1 μW. Experiments were also carried out to examine the effect of pulse length on the SHG conversion efficiency, and it was found that high-order nonlinear effects such as nonlinear refraction and two-photon absorption reduced substantially the efficiency at high power [99].…”
Section: Shg and Dfg By Means Of Dd-qpm In Periodically Intermixed Wamentioning
confidence: 99%
“…Several techniques have been developed to solve the problem of phase mismatch. Among those, we can list the realization of dispersionengineered waveguides with sub-micron dimensions (nanowires) [66] and the periodical modulation of either the linear [67] or nonlinear [68] optical susceptibility. In the next section,…”
Section: Algaas Strip-loaded Waveguidesmentioning
confidence: 99%